Two new species of the pseudoscorpion genus Lagynochthonius from China (Pseudoscorpiones: Chthoniidae) - Zhang, Fubin; Zhang, Feng (Entomologica Fennica, 2015)
Two new pseudoscrorpion species belonging to the genus Lagynochthonius of the family Chthoniidae are described from China: Lagynochthonius brachydigitatus sp. n., from Zhejiang Province, and L. medog sp. n., from Xizang Autonomous Region. Lagynochthonius microdentatus Hu & Zhang, 2012 is found to be a junior primary homonym of L. microdentatus Mahnert, 2011 and is replaced with Lagynochthonius harveyi Hu & Zhang, nom. n.